Discovery of Quinazolone Pyridiniums as Potential Broad-Spectrum Antibacterial Agents - Jie Dai; Qianyue Li; Ziyi Li; Zhonglin Zang; Yan Luo; Chenghe Zhou (Molecules)
The overprescription of antibiotics in medicine and agriculture has accelerated the development and spread of antibiotic resistance in bacteria, which severely limits the arsenal available to clinicians for treating bacterial infections. This work discovered a new class of heteroarylcyanovinyl quinazolones and quinazolone pyridiniums to surmount the increasingly severe bacterial resistance. Bioactive assays manifested that the highly active compound 19a exhibited strong inhibition against MRSA and Escherichia coli with extremely low MICs of 0.5 μg/mL, being eightfold more active than that of norfloxacin (MICs = 4 μg/mL). The highly active 19a with rapid bactericidal properties displayed imperceptible resistance development trends, negligible hemolytic toxicity, and effective biofilm inhibitory effects. Preliminary explorations on antibacterial mechanisms revealed that compound 19a could cause membrane damage, embed in intracellular DNA to hinder bacterial DNA replication, and induce metabolic dysfunction. Surprisingly, active 19a was found to trigger the conformational change in PBP2a of MRSA to open the active site, which might account for its high inhibition against MRSA. In addition, the little effect of molecule 19a on the production of reactive oxygen species indicated that bacterial death was not caused by oxidative stress. The above comprehensive analyses highlighted the large potential of quinazolone pyridiniums as multitargeting broad-spectrum antibacterial agents.